Analisis Komparatif Tingkat Manajemen Laba Berbasis Akrual dan Riil pada Perusahaan Industri Dasar dan Kimia yang Tergabung dalam Indeks Saham Syari’ah Indonesia (ISSI) - Khanifah Khanifah; Etna Nur Afri Yuyetta; Erwin Sa’diyah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
Earnings management is an effort by a company manager to intervene or influence information in financial statements with the aim of fooling stakeholders who want to know the performance and condition of the company (Sulistyanto, 2014). The purpose of this study was to compare the level of accrual and real earnings management in Basic and Chemical Industry companies listed in the Indonesian Syari'ah Stock Index (ISSI) in 2013-2016. In this study, accrual earnings manipulation was measured by variable discretionary accruals with the Jones modified model approach. Whereas for real earnings manipulation is measured through three variables, namely through operating cash flow, production costs and discretionary expenses with an approach developed by Roychowdhury, 2006. This research was conducted using secondary data in the form of financial statements. First, regression analysis was performed to find the estimated value of discretionary accruals, normal and abnormal values ​​of operating cash flows, production costs and discretionary expenses. Furthermore, descriptive statistics and comparative descriptive analysis were performed to compare accrual and real earnings management. The results of this study indicated that basic industrial and chemical companies incorporated in the Indonesian Shari'ah stock index (ISSI) in 2013-2016 tend to manipulated real earnings rather than through accrual activities with different patterns.